Association of Omega 3 and Omega 6 and Child Development: A Systematic Review - Diana, Fivi Melva; Fitria, Najmiatul (Nutrición Clínica y Dietética Hospitalaria, 2022)
Introduction: Omega-3 and omega-6 long chain polyunsaturated fatty acids (LCPUFA) are the major components of structural central nervous system. This study aimed to summarize the relationship between omega-3 and/ or omega-6 LCPUFA on children development. Method: Three large databases including Science Direct, Pubmed, and Cochrane were used to identify articles reporting the relationship of omega-3 and/or omega-6 and children development published between 2000 and 2021. The study was included if it was performed among under twelve children and provided the data of omega-3 and/ or omega-6 and cognitive development. This systematic review included both observational and experimental study. The publication bias was check using STROBE checklist. Results: The result showed that 4 articles were included consisted of 3 observational studies and 1 experimental study. Two observational studies reported a significant association between omega-3 and/ or omega-6 and children development. However, the experimental study did not confirm these findings. Publications bias was observed in methodology, where the findings showed a weakness in generalizability. Conclusion: This study concludes that omega-3 and omega-6 might play significant role in children development, but further study is needed to be done.